Nezami Ganjavi and Classical Persian Literature - Talattof, Kamran. author. aut Link
XII, 284 p. 7 illus.
Keywords: This book offers new insights into the twelfth-century Persian poet Nezami Ganjavi. Challenging the dominant interpretation of Nezami’s poetry as the product of mysticism or Islam, this book explores Nezami’s literary techniques such as his pictorial allegory and his profound conceptualization of poetry, rhetoric, and eloquence. It employs several theoretical and methodological approaches to clarify the nature of his artistic approach to poetry. Chapters explore Nezami’s understanding of rhetoric and literature as Sakhon, his interest in literary genres, the diversity of themes explored in his Five Treasures, the sources of Nezami’s creativity, and his literary devices. Exploring themes such as love, religion, science, wine, gender, and philosophy, this study compares Nezami’s works to other giants of Persian poetry such as Ferdowsi, Jami, Rudaki, and others. The book argues that Nezami’s main concern was to weave poetry rather than to promote any specific ideology. Kamran Talattof is Professor of Persian Literature and Iranian Culture at the School of Middle Eastern and North African Studies and affiliated with the Department of Gender and Women’s Studies at the University of Arizona, USA. He is also the Founding Chair of the Roshan Graduate Interdisciplinary Program in Persian and Iranian Studies. He has published widely across literature (modern and classical), Iranian and Middle Eastern culture, history and cinema, as well as Persian language pedagogy and translation.